1999
DOI: 10.1200/jco.1999.17.10.3313
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Advanced Malignancy by Direct Gene Transfer of an Interleukin-2 DNA/DMRIE/DOPE Lipid Complex: Phase I/II Experience

Abstract: Direct intratumoral injection of Leuvectin is a safe and possibly effective immunotherapeutic approach in the treatment of certain tumor types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 24 publications
2
43
0
1
Order By: Relevance
“…route. 14,22 A phase I trial in cancer patients with lung metastases confirmed intratumoral replication of the virus in lung metastases, 22 therefore, indicating that the first passage of the virus through the lungs after i.v. administration can be exploited to target viral delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…route. 14,22 A phase I trial in cancer patients with lung metastases confirmed intratumoral replication of the virus in lung metastases, 22 therefore, indicating that the first passage of the virus through the lungs after i.v. administration can be exploited to target viral delivery.…”
Section: Discussionmentioning
confidence: 99%
“…ONYX-015 in combination with MAP chemotherapy in sarcomas E Galanis et al administration of the IL-2 gene, 22 focusing on an immunotherapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…To address these problems, nonviral vectors, including cationic lipids or polycationic polymers, are attractive candidates because of their low immunogenicity, relative safety, and low cost. Direct intratumoral injection of IL-2 DNA/cationic lipid complex has been shown to be safe and efficient in patients with metastatic melanoma or metastatic renal cell carcinoma in clinical trials (13,14). However, the efficiency of these nonviral vectors for IL-2 gene delivery was lower than that of rAdv-IL-2.…”
Section: Introductionmentioning
confidence: 88%
“…CD8 + T cells were found to be the primary effectors, while CD4 + T cells did not appear to play a significant role in the development of tumor-specific immunity. In a phase I study followed by three phase I/II studies, RCC, melanoma, and sarcoma patients were treated with various concentrations of Leuvectin (Vical Inc., San Diego, CA) given once or twice weekly over 3 to 6 weeks [33]. Leuvectin contains a plasmid encoding human IL-2 formulated with the cationic lipid DMRIE/DOPE.…”
Section: Cytokine-based Immune Manipulationmentioning
confidence: 99%